ECONOMIC FOUNDATIONS OF SUSTAINABLE TOURISM AND WAYS TO DEVELOP IT - Mirzakhanova Sadiya Zamirbekovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
this article details the concept of Sustainable Tourism, its theoretical foundations, basic principles, types of infrastructure and its impact on local communities. Sustainable tourism is inextricably linked with economic, social and environmental factors, as well as analyzed in Uzbekistan on the example of directions for the development of this area, legislative foundations and strategic goals. The importance of transport, hotel, entertainment, information and personnel infrastructure is also shown. The article emphasizes the need for an integrated approach to the implementation of sustainable tourism.